Study on the unstable characteristics of high-level landslide in Zelongnong gou, Xizang under severe earthquakes - Junchen LIU; Wenpei WANG; Yang GAO; Jiawei WAN; Shaohua GAO (Zhongguo dizhi zaihai yu fangzhi xuebao)
The Zhelonglnong gou landslide in Xizang, located at high elevation with low intensity, has historically experienced significant instability due to strong earthquakes. To explore the dynamic response of the 1950 landslide to seismic events, this study employs FLAC3D dynamic simulations and bi-directional Milin earthquake acceleration records. The results show that the dynamic response is complex, influenced by slope geometry, material properties, and seismic wave intensity and frequency. At an elevation of 4000 m, glacial deposits exhibit compressive failure rather than failure at their leading edge. At 5500 m, the shear strain increment between glacial deposits and gneissic schist reaches its maximum, significantly higher than at the trailing edge of the glacial deposits. A sliding surface is identified between 4000 m and 5800 m, with a pull-and-shear failure type. To further analyze this instability pattern, resonance is considered, and the slope's natural frequency is found to range from 0.09 Hz to 1.89 Hz, with values of 0.2 Hz to 0.6 Hz between 4400 m and 5500 m. The seismic wave frequency closely matches the slope’s natural frequency in this range, resulting in significant resonance amplification. The amplification effect is stronger in gneissic schist than in glacial deposits.